Application Of Certainty Factor Method To Diagnose Gastroesophageal Reflux Disease (Gerd) - Putri, Raissa Amanda; Mayasari, Ulfayani; Yardha, La Saufa; Febiyaula, Siti Septia (International Conference on Sciences Development and Technology, 2021)
An expert system is a computer system that analyzes knowledge, reasoning techniques in problem solving and also facts by following the abilities of an expert. In the expert system there are several methods to help solve the problem, one of which is the certainty factor method or certainty factor which will later be used to solve the problem of gastric acid disease. Because using this method can increase the confidence of an expert. This study aims to design an expert system that will be useful for the community because it can diagnose acid reflux disease or GERD. The design of an expert system is intended to facilitate performance when replacing experts by a project that cannot afford to pay more.